Estimativa do tempo de vaporização das toras e sua implicação no desdobro e na secagem da madeira de Eucalyptus grandis - Calonego, Fred Willians [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
The present study to have to do as aim to determine the log steaming time its involvement on the sawing process and on the drying of Eucalyptus grandis wood. In order to do it so, were used logs with diameter of 20 at <25, 25 at <30 and 30 at <35 cm, from the Horto Florestal, Manduri, São Paulo. The logs were heated during 20 hours at 90ºC of temperature and 100% of relative humidity. For the adaptation of the logs heating general model developed by Steinhagen to make use of thermocouples fixed it logs center and a datalogger recorded the time and real temperature at each minute. Later the logs were sawing for width tangential system and measuring of the defects resulted from the growth stress were performed with intention to evaluate the effect of steaming treatment and the growth stress behavior with logs diameters. The sawn wood was dry in the dry-kiln and were available the dry defects of the sawn wood deriving as much the control logs as the steamed logs. The results indicate that: the log steaming time determination general model developed by Steinhagen don't is applied for eucalypts and that are necessary the use of the adjustment factors that provided the used them model for studied kind; the logs steaming provided the release of a great part of the growth stress, without, however, eliminate them completely, showing, nevertheless, that this treatment to be feasible and advisable for the growth stress relief; there are among the boards a difference on the growth stress magnitude with the logs diameters showing that the bigger logs to produce boards to be inclined cracks and that logs with diameter smaller to develop biggest boards opening during the sawing process; across of the drying schedules used so much boards provided of the control logs as the heated logs don't to presented collapse e that the warping and end checks were smaller in the heated material; the boards provided... (Complete abstract click electronic access below)
Keywords: Eucalyptus grandis - Crescimento; Toras de madeira - Vaporização; Madeira - Secagem; Eucalyptus - Growth; Eucalyptus grandis; Wood - Drying